THE RELATION BETWEEN TYPES OF IRON CHELATORS AND FERITIN ON OSTEOCALCIN OF THALASSEMIA PATIENTS WITH REPEATED TRANSFUSIONS - Amelia, Sesa; Nugroho, Trilaksana; Widyastiti, Nyoman Suci; Kholis, Fathur Nur (DIPONEGORO MEDICAL JOURNAL (JURNAL KEDOKTERAN DIPONEGORO), 2020)
Introduction:  Thalassemia is an inherited disorder that decrease the rate of globin synthesis. Multiple blood transfusions in thalassemia patients leading to complications of hemosiderosis and hemochromatosis. Iron chelator aims to remove excess iron in the body. High ferritin levels interfere with 25-hydroxyvitamin-D production and negatively affect bone metabolism, measured with osteocalcin (N-Mid Oc). Study aims to determine the relation between type of iron chelator and ferritin levels to osteocalcin levels in thalassemia patients with history of repeated transfusions. Method: An observational analytic cross-sectional study. Research was conducted in May - August 2019 and carried out at Red Cross Semarang, Rembang Hospital, and Purwodadi Hospital. Study subjects were 40 people, then 6 people were excluded to 34 people. Gender are 14 male and 20 female. Subjects were thalassemia patient with repeated transfusions and undergoing iron chelation therapy. Subjects that met the criteria were tested for blood to measure ferritin levels and osteocalcin levels. Results: Average ferritin levels was 2842.85 ug/L and average osteocalcin levels was 15.05 ng/mL. There was significant relation between type of iron chelator on osteocalcin levels (p=0.046), but there was no significant relation between type of iron chelator on ferritin levels (p=0.434). There was significant relation between ferritin levels and osteocalcin levels on patient with Deferasirox therapy (p=0.022), but no significant relation on patient with Deferiprone therapy (p=0.432). Conclusion: There is significant relation between the type of iron chelator on osteocalcin levels and there is significant relation between ferritin levels and osteocalcin levels on patient with Deferasirox therapy.Keywords: thalassemia,iron chelator, deferasirox, deferiprone, ferritin, osteocalcin